Microplastic surface biofilms: a review of structural assembly, influencing factors, and ecotoxicity - Chen, Hao; Wang, Xuewei; Yin, Haiyang; Sun, Le; Yang, Xinyan; Zhong, Wenyue; Kong, Lin; Liu, Ling (Frontiers in Marine Science, 2025)
As plastic pollution continues to escalate, the widespread presence and potential hazards of microplastics as an emerging global contaminant have drawn increasing attention. In natural environments, microplastic surfaces are prone to colonization by microbial biofilms composed of microorganisms and extracellular polymeric substances (EPS), forming a distinct microecosystem known as the plastisphere. This process not only modulates the physicochemical properties and environmental behavior of microplastics but also significantly changes their ecotoxicity. This paper systematically reviews the biofilm formation process on microplastic surfaces, the succession dynamics of microbial communities, and the key environmental and material factors influencing microbial colonization. On this basis, the regulatory modulates of biofilm formation on the physicochemical properties and environmental behavior of microplastics are analyzed, as well as their effects on bioavailability and ecotoxicological effects. Although there has been an increasing number of studies on the ecotoxicity of microplastics in recent years, most experiments are still limited to the pristine microplastics, that fail to reflect their realistic environmental exposure status. Therefore, this review emphasizes the necessity of incorporating biofilm-coated microplastics into toxicological assessments, to better simulate actual environmental conditions and to elucidate their synergistic roles in compound pollution scenarios.